Works written by Abu Lais Samarkandi in fiqh (Islamic jurisprudence) and other fields (Eurasian Scientific Herald, 2022)
The life and scientific activity of one of the famous Hanafi scholars of Movarounnahr, the scholarAbu Lais Samarkandi, has been widely studied by many researchers of our motherland andforeign countries. In these studies, the scholar is presented as a famous Islamic jurist and mufassir(translator and commentator of the Holy Qur’an and its meanings). This article pays specialattention to the study of the aspects of Abu Lais Samarkandi's scientific heritage in kalam (Qur’an)knowledge. His contribution to the development of Moturidism as one of the hanafi-moturidischolars was revealed